Sovereignty and the limits of the liberal imagination [ - Nelson, Scott G. (Routledge, 2009)
A study of the concept of sovereignty in the modern epoch. It asks how each are effected in history through liberal-Enlightenment ethical and political affirmations which anchor themselves in a unique metaphysics of statecraft